Speech Act Analysis of Promotional Content for Skin Care Products on Tiktok - Survey Sijabat; Jacobus Rico Kuntag; Arin Mantara Anggawirya; Evelin Giovani; Abdullah (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze speech act in promotional content for skin care products on TikTok based on John R. Searle’s speech act theory. It uses a qualitative approach with a pragmatic analysis design. The research data consist of utterance units found in captions, visual video text, voice-over narration, and spoken utterances in TikTok content uploaded by brand accounts. Data were collected through documentation techniques, while the data were selected purposively based on content suitability, the presence of promotional utterances, contextual clarity, and the feasibility of pragmatic analysis. From 389 initial utterance units, 205 units were selected as core data after the data-cleaning process. The findings show that representative/assertive speech acts are the most dominant category, with 131 units or 63.9%, followed by directive speech acts with 48 units or 23.4%, commissive speech acts with 16 units or 7.8%, and expressive speech acts with 10 units or 4.9%. Declarative speech acts were not found in the data. These findings indicate that promotional content for skin care products on TikTok is constructed primarily through benefit claims, product information, usage experiences, and solution statements, which are then reinforced by invitations, recommendations, warnings, offers, and evaluative expressions.